The Role of Mondo Family Transcription Factors in Nutrient-Sensing and Obesity - Ke, Huiyi; Luan, Yu; Wu, Siming; Zhu, Yemin; Tong, Xuemei (Frontiers in Endocrinology, 2021)
In the past several decades obesity has become one of the greatest health burdens worldwide. Diet high in fats and fructose is one of the main causes for the prevalence of metabolic disorders including obesity. Promoting brown or beige adipocyte development and activity is regarded as a potential treatment of obesity. Mondo family transcription factors including MondoA and carbohydrate response element binding protein (ChREBP) are critical for nutrient-sensing in multiple metabolic organs including the skeletal muscle, liver, adipose tissue and pancreas. Under normal nutrient conditions, MondoA and ChREBP contribute to maintaining metabolic homeostasis. When nutrient is overloaded, Mondo family transcription factors directly regulate glucose and lipid metabolism in brown and beige adipocytes or modulate the crosstalk between metabolic organs. In this review, we aim to provide an overview of recent advances in the understanding of MondoA and ChREBP in sensing nutrients and regulating obesity or related pathological conditions.